The impact of cognitive distraction on gustatory perception in volunteers with obesity - Ruda, Iryna; Chellapandian, Deepak Charles; Freiherr, Jessica (Scientific Reports, 2024)
Obesity, a global health challenge, is influenced by biological, behavioral, socioeconomical, and environmental factors. In our technology-driven world, distracted eating is prevalent, yet neurocognitive mechanisms behind it remain poorly understood. This study targets individuals with overweight and obesity, exploring taste perception under distraction comprehensively. Participants formed two distinct groups based on their Body Mass Index (BMI), lean and overweight/obese. During the experiment participants received gustatory stimuli while playing a Tetris game of various difficulty levels. Participants rated taste intensity and pleasantness, with linear mixed models analyzing distraction effects. Results confirmed that high distraction levels reduced perception of taste intensity (p = 0.017) and taste pleasantness (p = 0.022), with variations influenced by gender and weight status. Individuals in the overweight/obese group exhibited most profound intensity changes during distraction (p = 0.01). Taste sensitivity ratings positively correlated with BMI interacting with gender (male r = 0.227, p < 0.001; female r = 0.101, p < 0.001). Overall across both groups, female participants demonstrated higher taste sensitivity compared to male participants (p < 0.001). This study highlights the impact of cognitive distraction during consumption on taste perception, particularly in relation to weight status and gender, underscoring their significant roles in this interplay.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Distracted eating; Gustatory perception; Intensity; Obesity; Pleasantness